BIOLOGICAL ACTIVITY OF STEROIDAL GLYCOSIDES FROM BULBS OF ALLIUM CYRILLII TEN. (ALLIACEAE) - N. V. Tolkachova; E. Z. Komarovskaya-Porokhnyavets; V. P. Novikov (Фармация и фармакология (Пятигорск), 2015)
Biological activity of steroidal glycosides from the bulbs of Allium cyrillii Ten. have been investigated. It is shown that they have not possess bactericidal properties, but have high fungicidal and growth-regulatory activity.